PERLAKUAN BENIH, PENCANGKOKAN DAN STEK PUCUK Eusideroxylon zwageri T.et.B. (Seed Treatment, Air Layering and Stem Cutting of Eusideroxylon zwageri T.et.B.) - , Fx. Dwisutanto ([Yogyakarta] : Fak. Kehutanan UGM, 2000)
Ulin or kayu besi (Eusideroxylon zwageri T.et.B) is an important timber species in East Kalimantan. However, there are problems in the regeneration of this species. Mechanical method for seed scarification by cutting at the seed end where radicle emerges provided the best germination percentage (100 %) compared with untreated seed (75 %). while sulphuric acid (H2SO.) had very detrimental effect on germination (0 %). Air layering method could be utilized to propagate genetically superior individuals and to increase forest production. The use of IBA I % gave higher success rate compared with without hormone treatment, even though statistically not significant. Branch diameter larger than 3 cm resulted in complete failure of the branch to root. With regard to stem cutting the application of Root one F at rates of500 - 1000 ppm gave the highest rooting ability (80 - 84 %), while no hormone treatment only resulted in 69 % of the shoot to have roots.